Pengalaman Pasien Guillain-Barre Syndrome Selama Fase Hospitalisasi - Trisyani, Yanny; Susanti, Vera; Muhaemin, Muhaemin; Winara, Winara; Risnianingsih, Nina; Putri, Saparingga Dasti; Tambunan, Natalia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Guillain-Barré Syndrome (GBS) is a rare autoimmune condition that can lead to muscle weakness and total paralysis, often occurring following an infection. The hospitalization phase for GBS patients can significantly impact their mental health and recovery process. This study aims to map the literature concerning the subjective experiences of GBS patients during hospitalization, identify the challenges they face, and understand the psychosocial impacts and the support needs required. The methodology employed is a scoping review based on the Arksey and O'Malley framework, with data gathered from three primary databases: PubMed, Scopus, and Medline. Inclusion criteria include studies reporting on subjective experiences during hospitalization, primary studies employing qualitative, quantitative, or mixed-method approaches, and articles published in English within the last ten years (2015-2024). Eight articles met the inclusion criteria, and the analysis showed that GBS patients experience significant physical, psychological, and social challenges, as well as complex interactions with healthcare providers. These findings underscore the importance of clear communication and emotional support during care, while also identifying gaps in the existing research. Recommendations for further research include the development of interventions that are more responsive to the needs of GBS patients, aimed at improving the quality of care and patient experiences during hospitalization. Keywords: Guillain-Barre Syndrome, Experience, Hospital.